Implementation of Authentic Assessment by Teachers in the Independent Curriculum for English Reading Skills at SMAN 16 Makassar - Pidia Warahma; Hikma Patika Sari; Dzulqarnain Dzulqarnain Rahmat (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
This study aims to explore the implementation of authentic assessment in English reading instruction based on the Independent Curriculum (Kurikulum Merdeka) through semi-structured interviews with an English teacher at SMAN 16 Makassar. Employing a qualitative descriptive design, data were collected through a semi-structured interview instrument comprising eight open-ended questions, audio-recorded and transcribed manually for thematic analysis. Using a qualitative descriptive approach, this study explores the teacher's understanding, the types of tasks used, student engagement, challenges faced, and their alignment with curriculum objectives. The results indicate that the teacher implemented authentic assessment primarily through oral reading activities, vocabulary development, and performance-based observations. These strategies reflect language use in real contexts and support student-centered learning. Despite facing challenges such as students' pronunciation difficulties due to regional dialects, the teacher implemented adaptive strategies such as repetition, inclusive feedback, and the use of flexible assessment tools such as rubrics and stopwatches. The study concludes that although the current implementation is still rudimentary, the practice aligns with the principles of the Independent Curriculum, which emphasize flexibility, engagement, and competency-based assessment. This study highlights the importance of implementing contextual and inclusive assessment to meaningfully improve students' reading skills. It is recommended that teachers diversify authentic assessment tasks by incorporating reading journals, portfolios, and peer review activities to more comprehensively evaluate students' reading competencies in line with the Independent Curriculum.